A família no processo de construção social de mercados: uma análise da constituição moral do trabalho livre na economia cafeeira de São Carlos - Palma, Rogério da (Universidade Federal de São Carlos, 2010)
Family relationships acquired fundamental importance in the labor process of the coffee economy of the "new" west of São Paulo, but it is not yet known systematic study on how they acted in the occupational structure of Italian and Brazilian blacks. Through consultation with a municipal census and police investigations, this study has as its purpose the analysis of family configuration and perceptions about the family between Italian and Brazilian blacks coffee plantation located in the San Carlos during the turn of the nineteenth century to the twentieth century. Based on the idea that markets are social constructs, we tried to help understand the historical formation of the free labor market in question. At first, it was perceived through the examination of data on family configuration of blacks and Italians, the exercise of greater control by the Italians, to the residence of married children with families. This may demonstrate that they possessed a family project more consolidated around the colonato. We were able to delineate the moral assumptions also similar in the speeches of both categories studied. It was evident, however, the fact of experience around these assumptions to be quite different between them. The process of racialization of the period covered relegated to black representation contrary to morality family seen as conducive to the free labor market. It is believed that, together with the further consolidation of the colonato as a family project among Italians, this pre-concept with the family morality of african descent is crucial to explain the positioning of this social category in the labor market free of coffee economy of São Carlos.
Keywords: Sociologia econômica; Família; Negros; Italianos; Oeste paulista; Mercado de trabalho; CIENCIAS HUMANAS::SOCIOLOGIA